Exporters and global value chain participation: Firm-level evidence from South Africa - Caio Torres Mazzi; Gideon Ndubuisi; Elvis Korku Avenyo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Using the South African Revenue Service and National Treasury firm-level panel data for 2009-17, this paper investigates how global value chain-related trade affects the export performance of manufacturing firms in South Africa. In particular, the paper uses extant classifications of internationally traded products to identify different categories of global value chain-related products and compares the productivity premium of international traders for these different categories. Also, the paper investigates possible differences in learning-by-exporting effects across the identified categories of global value chain-related products by estimating the effect of exporting before and after entry into foreign markets. The results confirm that global value chain-related trade is associated with a higher productivity premium compared with traditional trade. However, within the categories of exporters, only the firms that trade in global value chain-related products and simultaneously engage in research and development in the postentry periods appear to learn from exporting.
Keywords: F12; F14; O3; O33; 330; global value chain; learning-by-exporting; productivity premium; South Africa